2020
DOI: 10.1097/ccm.0000000000004075
|View full text |Cite
|
Sign up to set email alerts
|

Acute Respiratory Distress Syndrome Following Pediatric Trauma: Application of Pediatric Acute Lung Injury Consensus Conference Criteria

Abstract: Objective: To assess the incidence, severity, and outcomes of pediatric acute respiratory distress syndrome (PARDS) following trauma using Pediatric Acute Lung Injury Consensus Conference criteria Design: Retrospective cohort study Setting: Level 1 pediatric trauma center Patients: Trauma patients ≤17 years admitted to the intensive care unit from 2009-2017 Interventions: None Measurements and Main Results:We queried electronic health records to identify patients meeting PARDS oxygenation criteria for ≥6 hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 29 publications
0
33
1
Order By: Relevance
“…Since PALICC, many studies have corroborated the impact of previously identified comorbidities—most notably immunodeficiency (1–21)—and PARDS triggers (22–81) on severity of PARDS or PARDS outcomes. It remains clear that both comorbidities and the many conditions that cause PARDS contribute to the heterogeneity seen in this syndrome.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Since PALICC, many studies have corroborated the impact of previously identified comorbidities—most notably immunodeficiency (1–21)—and PARDS triggers (22–81) on severity of PARDS or PARDS outcomes. It remains clear that both comorbidities and the many conditions that cause PARDS contribute to the heterogeneity seen in this syndrome.…”
Section: Resultsmentioning
confidence: 93%
“…Furthermore, there has yet to be an effective pharmacologic treatment for PARDS, and care is supportive. In addition, PARDS is a heterogeneous condition due in part to differences among children in the underlying pathobiology, age (which impacts changes in the lungs, chest wall, and immune system associated with development), comorbidities (1–21), and inciting trigger (22–85).…”
mentioning
confidence: 99%
“…The incidence of ARDS was very low in our cohort, and that could be explained by two reasons. First, the retrospective design did not allow us to precisely assess the Berlin criteria a posteriori while ARDS is probably underestimated and underreported [ 6 ]. Second, as assessed by the trauma severity scores we used, patients included in our cohort are overall less severe than patients reported in other observational studies [ 17 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Iatrogenic withdrawal syndrome was defined as having a highest daily Withdrawal Assessment Tool-1 score greater than or equal to 3 (23). Pediatric Acute Respiratory Distress Syndrome (PARDS) severity was defined using the Pediatric Acute Lung Injury Consensus Conference criteria (24). Multiple Organ Dysfunction Syndrome (MODS) was defined as one or more extrapulmonary organ dysfunctions.…”
Section: Methodsmentioning
confidence: 99%